Relevansi: peran Ayah dalam tumbuh kembang anak dengan fenomena fatherless yang ada di Indonesia - Maknun, Hurin In (Maliki Interdisciplinary Journal, 2025)
The phenomenon that is currently rife that has named Indonesia as number three in the world is its contribution to the lack of fatherhood in the family. Fathers are not just breadwinners in the family, but also have an obligation to care for the growth and development of their children. The importance of the father’s role in the family is proven by how much impact it has on the child if this obligation is not fulfilled. Fatherlessness also impacts children’s academic performance, reduces self-control in adolescents, and makes it difficult for girls to build social relationships. In some cases, children are single-parented, meaning both parents are excluded from their development. The continued decline in the father’s role in parenting can have serious consequences, such as decreased cognitive abilities, juvenile delinquency, and difficulty establishing and maintaining healthy social relationships with others.